2013
DOI: 10.1590/s0102-86502013000900007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brassica oleracea in rats skin wound healing

Abstract: PURPOSE:To investigate the effect of Brassica oleracea herbal balsam on the healing of skin wounds in rats. METHODS:Twenty four rats (Wistar, 60 days, 250 g) were divided into four groups: untreated animals (C) and treated with the ointment (T), subdivided into two experimental times (seven and 16 days). A 3cm 2 skin wound was made in the back of all animals.100 ml of the Brassica oleracea was applied twice a day in T group. Biometric analysis was made with images captured at one, four, seven, ten, 13, and 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…Wound healing is a complex biological process involving cellular and chemical responses, with the initial purpose of reorganizing the extracellular matrix components with the objective of rapid wound closure, in addition to the obtaining of a functional and aesthetically satisfactory scar. 1,2 Although there is no epidemiological data on this in Brazil, alterations in skin integrity affect the quality of life of sufferers and constitute a serious public health problem as they have physical, psychological and social impacts, coupled with high economic costs. 3 Studies of platelet-rich plasma (PRP) focus on the evaluation of their growth factors, which are important in the repair of wounds during healing and are released through platelet degranulation.…”
mentioning
confidence: 99%
“…Wound healing is a complex biological process involving cellular and chemical responses, with the initial purpose of reorganizing the extracellular matrix components with the objective of rapid wound closure, in addition to the obtaining of a functional and aesthetically satisfactory scar. 1,2 Although there is no epidemiological data on this in Brazil, alterations in skin integrity affect the quality of life of sufferers and constitute a serious public health problem as they have physical, psychological and social impacts, coupled with high economic costs. 3 Studies of platelet-rich plasma (PRP) focus on the evaluation of their growth factors, which are important in the repair of wounds during healing and are released through platelet degranulation.…”
mentioning
confidence: 99%
“…In the conventional medicine articles, there is some evidences of positive effect of these plants on the wounds. A study in Brazil in 2013 found that an ointment made from the cabbage extract, accelerated wound healing by mechanism of increasing collagen type 1 fibers [15]. In the case of marshmallow, its effects on increasing the gene expression associated with specific cell adhesion proteins, growth regulators, extracellular matrix, cytokine release and apoptosis have been proven.…”
Section: Discussionmentioning
confidence: 99%
“…However, the synthesis of this component of the matrix was connected to good tissue vascularization that provided oxygen and nutrients to the tissue for optimal metabolic activity of the fibroblasts and was more abundant and important for cell synthesis of the matrix components [ 2 , 37 , 38 ]. In addition to flavonoids, the compounds and phytochemicals in the B. oleracea extract included phenols, sulforanos, and anthocyanins [ 27 , 28 , 39 ], which had a positive effect on collagen type I expression and gradually influenced a reduction in the expression of collagen type III [ 28 ].…”
Section: Discussionmentioning
confidence: 99%